Generating XML from relational database tables prepare for the future. - Mimaroglu, Selim
This article looks in detail at how to generate XML data from your relational database. Although the examples were run on Oracle, very lttile of the code is Oracle specific. You can easily use all the ideas and examples presented here in other relational databases. We did this project at University of Massachusetts Boston as part of the Electronic Field Guide (EFG) project.